The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.jses.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3-dimensionally printed patient-specific guide improves accuracy compared with standard total shoulder arthroplasty guide: a cadaveric study

Abstract: Background Patient-specific instrumentation (PSI) systems for total shoulder arthroplasty (TSA) can improve glenoid component placement, but may involve considerable expense and production delays. The purpose of this study was to evaluate a novel technique for in-house production of 3-dimensionally printed, patient-specific glenoid guides. We hypothesized that our PSI guide would improve the accuracy of glenoid guide pin placement compared with a standard TSA guide. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…Another issue is that the trigonum positioning and the overall morphology of the global medial side of the scapular blade is highly variable and leads to more difficulties in identifying this medial landmark. Moreover, in the literature, authors give different definitions of the trigonum that can be the most medial point of the scapula [ 33 , 34 ] or the intersection between the spine and the medial border of the scapula [ 22 , 26 , 35 , 36 ] (the definition we have chosen in our article). It can also be termed “trigonum scapulae” [ 34 , 37 , 38 ], “trigonum spinae” [ 39 ] or “os trigonum” [ 40 ] with no further precision.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue is that the trigonum positioning and the overall morphology of the global medial side of the scapular blade is highly variable and leads to more difficulties in identifying this medial landmark. Moreover, in the literature, authors give different definitions of the trigonum that can be the most medial point of the scapula [ 33 , 34 ] or the intersection between the spine and the medial border of the scapula [ 22 , 26 , 35 , 36 ] (the definition we have chosen in our article). It can also be termed “trigonum scapulae” [ 34 , 37 , 38 ], “trigonum spinae” [ 39 ] or “os trigonum” [ 40 ] with no further precision.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis of Cabarcas et al also reported no significant differences in accuracy between PSI and standard instrumentation 24 . Furthermore, PSIs take time and cost to make after planning and are not used in all patients 25 .…”
Section: Discussionmentioning
confidence: 99%
“…26 3. Incremento de la precisión quirúrgica: Cabarcas y colaboradores 27 demostraron en un estudio cadavérico aleatorizado que el uso de instrumental específico en artroplastías de hombro incrementó la precisión en la inserción del pin glenoideo en comparación con las guías estándar. En otro estudio, 46 pacientes con artrosis glenohumeral avanzada fueron asignados aleatoriamente a plantillas preoperatorias de tomografía computarizada tridimensional con instrumentación estándar o con instrumentación específica y se compararon con un grupo de 17 pacientes con imágenes bidimensionales e instrumentación estándar utilizados como control.…”
Section: Aplicaciones En Ortopedia Y Traumatologíaunclassified